P09.04 Cathepsin V inhibition prevents the activation of cystatin F and increases immune cell cytotoxicity. (21st September 2022) - Senjor, E; Mitrović, A; Jukić, M; Proj, M; Perišić Nanut, M; Gobec, S; Kos, J
Abstract : Background: Cysteine cathepsins C, H, and L are important mediators of granule-dependent cytotoxicity of natural killer cells and cytotoxic T lymphocytes as they enable activation of granzymes and perforin, which execute cytotoxic effects on cancer cells. Cystatin F plays a central role in the regulation of cathepsins in cytotoxic immune cells. This type II family cystatin can be translocated to endo/lysosomes or secreted and further internalized into bystander cells due to the glycosylation. In the lysosomes it is activated from inactive dimeric form to active monomer by cathepsin V, which cleaves 15 N-terminal amino acids from cystatin F. Cystatin F is normally expressed by immune cells, however, in tumor microenvironment it was found to be increased also in non-immune cells. The increased levels of cystatin F may contribute to the immunosuppressive status of the tumor microenvironment. We evaluated the effects of cathepsin V inhibition on the cytotoxicity of immune effector cells NK-92 and TALL-104. Materials and Methods: To discover cathepsin V inhibitor, molecular docking was used to evaluate interactions of small molecular compounds from commercial libraries with cathepsin V. A set of selected compounds was evaluated by enzyme kinetics for the inhibition of recombinant cathepsin V, selectivity and reversibility of binding to the target. The most potent, selective and reversible acting compound was tested in functional assays. The effect of cathepsin V inhibition on cystatin F activation was tested with western blot. Calcein-AM release assay was used to evaluate the effect on immune cell cytotoxicity. Results: After molecular docking and biochemical evaluation, we selected the most potent, selective, and reversible ureido methylpiperidine carboxylate derivative as inhibitor of cathepsin V. Next, we tested the effect of the selected compound on cystatin F activation in cytotoxic immune cells. The cystatin F dimer-to-monomer ratio was increased after treatment with both broad-spectrum peptidase inhibitor E-64d and after treatment with the selective reversible cathepsin V inhibitor. As expected, treatment of immune effector cells with E-64d decreased cytotoxic function, as this inhibitor impairs the activities of all cathepsins including cathepsins C, H, and L. However, treatment of cytotoxic cells with cathepsin V inhibitor increased their cytotoxicity. Conclusions: Selective inhibition of cathepsin V prevents the monomerization and activation of cystatin F. By targeting the activating protease of cystatin F, we can reduce the detrimental effects of cystatin F on cytotoxic cells in the tumor microenvironment. Disclosure Information: E. Senjor: None. A. Mitrović: None. M. Jukić: None. M. Proj: None. M. Perišić Nanut: None. S. Gobec: None. J. Kos: None.